The Impact of Epidural Analgesia on Postoperative Outcome After Major Abdominal Surgery - Cindea, Iulia; Balcan, Alina; Gherghina, Viorel; Samoila, Bianca; Costea, Dan; Grasa, Catalin; Nicolae, Gheorghe (IntechOpen, 2012)
None